Pengaruh Motivasi Kerja, Disiplin Kerja, dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT Gading Semesta Utama - Muhammad Dhaifan Rhamdani; Diana Hasan (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Employee performance plays a crucial role in determining organizational success, including in construction and material supply companies such as PT Gading Semesta Utama. Although employee performance indicators over the past three years have shown an upward trend, several aspects related to discipline and service orientation have not yet reached optimal levels. This condition indicates a gap between performance outcomes and internal human resource factors that influence them. Therefore, this study aims to empirically examine the effect of work motivation, work discipline, and job satisfaction on employee performance at PT Gading Semesta Utama. This study employs a quantitative approach with an associative research design. The research population consists of all employees of PT Gading Semesta Utama, with a saturated sampling technique applied, resulting in the entire population being used as the research sample. Data were collected through structured questionnaires using a Likert scale and analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that work motivation has a positive and significant effect on employee performance, while work discipline shows a negative and insignificant effect. In contrast, job satisfaction has a positive and significant influence on employee performance. These findings suggest that employee performance improvement is more strongly driven by motivational and satisfaction factors than by formal disciplinary mechanisms. The study provides practical insights for organizations in formulating human resource policies that emphasize psychological and motivational aspects to enhance employee performance.